OP099: Management of the temporomandibular joint after ablative surgery – A risk based algorithm - Bredell, Marius; Grätz, Klaus; Obwegeser, Joachim; Gujer, Astrid Kruse (Oral oncology, 2013)
Management of the temporomandibular joint (TMJ) in ablative head and neck surgery is controversial with no standard approach being advocated. Reconstruction options range from complete joint replacement, free vascularised grafts to osseodistraction. Analysis of all patients’ records receiving ablative surgery involving the temporomandibular joint in the department of Craniomaxillofacial and Oral Surgery, University Hospital of Zürich from 2000 to 2012 was performed. Thirteen patients were identified with all patients receiving temporomandibular joint surgery due to internal derangement or trauma being excluded. Furthermore a Medline and Pubmed based literature search was done identifying all current approaches in the management of the temporomandibular joint and analyzing all case series. Seven studies with acceptable data were selected. A wide variety of procedures have been described ranging from no reconstruction to total prosthetic joint reconstruction. Studies were not uniform in their reporting, lacking statistical power with non-homogeneous patient groups. Despite these limitations, the literature based experience correlated with risk factors in our series. Risk factors appear to be radiation, costo-chondral graft, disk loss and plate use alone. Most common complications were plate exposure and occlusal disturbance. Fibula free vascular grafts appeared to have the least complications. On clinical experience and literature evidence a risk based flow chart was developed depicting surgical risk based options. Risk factors like radiation, disk loss, the potential use of plate only or costo-chondral graft use are important when planning surgery where partial or complete ablative surgery of the temporomandibular joint is planned. Fibula free vascularised grafts appear to have the least complications that have to be weighed against the donor site morbidity.